PERANAN HUKUM DALAM PEMBANGUNAN EKONOMI DI BIDANG TENAGA KERJA DI TENGAH PENERAPAN PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) DI INDONESIA - Ravellino, Fransiskus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
At the beginning of the year 2020 , Indonesia is experiencing a new phenomenon of is not fed, the phenomenon of pandemic covid-19 .Up to january 2021 , there is at least 808.000 covid-19 people infected with the virus , as many as 667.000 of them they cured and 23.753 soul that have died .The speed of the transmission of the virus coupled with the community apply protocol disiplinan is typical of the health make pandemic virus covid-19 it is difficult to overcome and forcing the administration to apply large scale social restrictions (PSBB) and this might impact on the economic growth of indonesia one of them is many unemployment due to reduced the company capacity to maintain labor that is .This research aims to review and give feedback about the role of the law into economic development especially in in the field of labor in the middle of this large-scale social restriction (PSBB) in the middle of this pandemic.